Cannabis Phytomolecule 'Entourage': From Domestication to Medical Use. (October 2020) - Koltai, Hinanit; Namdar, Dvora
Abstract : Cannabis has been used as a medicine for millennia. Crude extracts of cannabis inflorescence contain numerous phytomolecules, including phytocannabinoids, terpenes, and flavonoids. Combinations of phytomolecules have been recently established as superior to the use of single molecules in medical treatment owing to the 'entourage effect'. Two types of entourage effects are defined: 'intra-entourage', resulting from interactions among phytocannabinoids or terpenes, and 'inter-entourage', attributed to interactions between phytocannabinoids and terpenes. It is suggested that the phytomolecule assemblages found in cannabis chemovars today derive from selective breeding during ancient cultivation. We propose that the current cannabis chemotaxonomy should be redefined according to chemical content and medicinal activity. In parallel, combinations of phytomolecules that exhibit entourage activity should be explored further for future drug development. Highlights: Cannabis has been used for millennia by humanity for social, ritual, and medical purposes. Humans bred and selected for cannabis strains based on their needs. Today, patients are treated by cannabis 'strains', without a clear definition of activity or known chemical content. Cannabis sativa strain taxonomy is based on the content of two phytocannabinoids only, Δ 9 -tetrahydrocannabinolic acid (THCA) and cannabidiolic acid (CBDA). C. sativa produces hundreds of phytomolecules, including phytocannabinoids, terpenes, and flavonoids. Some cannabis phytomolecules interact, causing enhanced biological activity. Defining this phenomenon, known as the 'entourage effect', is one of the leading challenges in the field of research.